Estimating Burden of Disease Among Blind Individuals With Non-24-Hour Sleep-Wake Disorder - Van Draanen, Lauren; Xiao, Changfu; Polymeropoulos, Mihael H. (Frontiers in Neurology, 2021)
Estimating Burden of Disease among blind individuals with Non-24-Hour Sleep-Wake Disorder Abstract Purpose– To quantify the burden of disease in blind patients with Non-24-Hour Sleep- Wake Disorder (N24HSWD), utilizing longitudinal sleep diary data. N24HSWD is a circadian disorder characterized by a cyclical pattern of aberrant circadian and sleep-wake cycles that are associated with increased frequency of sleep episodes during the school/work day hours. Daytime sleep episodes would be predicted to decrease the opportunity for school/work participation, significantly impacting the quality of life of the patient. Methods— We used the sleep diary data of daytime sleep from a period of approximately 90 days in blind individuals that presented with a sleep complaint. These subjects were identified from a group of blind individuals with N24HSWD (n=121) and a control group of blind individuals without N24HSWD (n=57). Results— N24HSWD patients had more frequent and longer episodes of daytime sleep as compared to a control group. Using duration of daytime sleep as a surrogate for defining a healthy or unhealthy day, N24HSWD patients also had significantly fewer healthy days, defined by daytime sleep free days (DSFD), days without a sleep episode between 9:00 AM and 5:00 PM, as compared to the control group. Conclusion— Daytime sleep free day (DSFD) is a useful and specific measure of disease burden in patients with N24HSWD and it is predicted to be correlated with the standardized HRQOL-4, Healthy Days measurement.